(untitled) (Economic and Political Thought, 2016)
Since the ‘January 25 Revolution’ the Egyptian territory has become a subject of increased interest of various jihadist structures. The Sinai Peninsula plays a special role in their development as it is an area of strategic importance because of its proximity to Israel and Cairo, one of the centers of the Arab world. Among such structures there is Sinai Province, which is a relatively new player on the scene of the Egyptian political violence, although now this entity has the greatest influence on this territory. The group derives from Ansar Bayt al-Maqdis, a group that appeared in the northern part of the Sinai Peninsula in 2011. In 2013 it transformed into a branch of the Islamic State. Despite significant operational capabilities, Sinai Province is not the only jihadi structure functioning in Egypt. New armed groups opposed to state structures are formed, which include Ajnad Misr or the Allied Popular Resistance Movement. The article aims to present the process of jihadism expansion in Egypt after 2011, tying it with destabilisation of the state’s internal structures, reflected by frequent changes of authorities.